EFEKTIVITAS METODE PEMBERIAN TUGAS TERHADAP PENGETAHUAN MINAT BELAJAR SMA NEGERI 4 SUNGAI RAYA - Septino, Yuvensius; .H Mastum, Junaidi; Aminuyati, Aminuyati (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis study aims to examine the lack of effectiveness in the selection of learning methods. "Effectiveness of the Implementation Method of Giving Tasks to the Improvement of Student Learning Knowledge in Ecomoni Subjects in Class X IPS of SMA Negeri 4 Sungai Raya". Having a problem statement Are there differences in students' knowledge of economic subjects, Are there differences in students' interests in economic subjects, Which learning method is more effective between assignment methods and conventional learning by increasing students' knowledge and interest in learning in economic subjects. This research is using experimental method . As for the source of the data used is direct observation with the process of observation and writing of symptoms that arise in the study. Data will be analyzed by descriptive analysis method. The theoretical foundation used in the research is the method of assigning tasks, knowledge, and interests. Based on the analysis conducted, it was concluded that there are differences in learning with the assignment method of learning knowledge, there is no difference in learning with the assignment method to interest in learning, an effective learning method that is using the assignment method.Keywords, Effectiveness, Knowledge, Learning Interest, Assignment Method.